Gait and frontal lobe function become associated in patients with idiopathic normal pressure hydrocephalus after shunt surgery - Ishikawa, Masatsune; Mori, Etsuro; Kazui, Hiroaki (Frontiers in Neurology, 2025)
ObjectiveThe association between gait and cognition in older adults is well-established. This study investigated the association between gait and cognition, especially in the frontal lobe, in patients with idiopathic normal pressure hydrocephalus (iNPH). Studies using cognitive assessment batteries often treat grading scores as continuous; however, these scores are inherently ordinal, which may lead to inaccurate results. To address this, a generalized additive model with an ordinal smoothing penalty was applied to analyze the data, including the ordinal scale.MethodsThis supplementary study is based on an open-labelled clinical trial, SINPHONI-2, which was designed to evaluate the effectiveness of lumboperitoneal shunting in patients with probable iNPH. Gait and frontal lobe function were assessed using the Timed Up-and-Go (TUG) test and Frontal Assessment Battery (FAB), respectively. Sixty-nine patients with available pre- and postoperative data were selected.ResultsCompared to the preoperative values, TUG time showed statistically significant improvement at 3,6, and 12 months after surgery. The FAB total score, analyzed as continuous data, became significant at 6 months postoperatively. When the FAB task scores were analyzed as ordinal data, TUG time was significantly associated with the “motor programming” and “conflicting instructions” tasks at 3, 6, and 12 months. The “environmental autonomy” task showed a significant association at 6 and 12 months, and the “verbal fluency” task at 12 months. In contrast, no association was found for the “conceptualization” and “inhibitory control” tasks. Analyses using a generalized additive model revealed that most relationships between TUG time and FAB task scores were linear, although some were non-linear.ConclusionThe associations between TUG time and FAB task performance gradually strengthened over the first year after surgery. FAB tasks involving hand movements were significantly associated with improvements in gait. This analytical approach can be applied to datasets with ordinal predictors in various research fields, such as grading scales used to assess disease severity.